Research of the Adequacy of the Conceptual Model of Non-Traditional Education to the Traditional Educational Process - Alimnazarov Olim (International Journal on Integrated Education, 2022)
This article covers the issues of improving the methodology for researching the adequacy of the conceptual model of non – traditional education to the traditional educational process through mathematical modeling of the educational process.